Problems and Countermeasures of “Internet plus” Marketing in Home Appliance Industry -- Taking Gree Electric Appliance as an Example - Xiong Xinyi (SHS Web of Conferences)
This study takes Gree Electric Appliance as an example to analyze the problems encountered in the implementation of “Internet plus” marketing in the home appliance industry and put forward corresponding countermeasures and suggestions. This article first points out the problems that Gree Electric has in terms of user experience on its official website, the contradiction between excessive personal IP traces and company development, structural drawbacks of its management, and insufficient appeal to young consumers. Then, aiming at these problems, this research proposes the following solutions: optimizing the official website structure, balancing personal IP and brand independence, and strengthening internet promotion. This paper believes that through these measures, Gree Electric can avoid the loss of its core competitiveness in the home appliance industry in the future, effectively improve the “Internet plus” marketing effect, enhance the brand image, increase the attractiveness to young consumers, promote the sustainable development of enterprises, and provide a certain reference value for the future development of the household appliance industry.